2011
DOI: 10.1139/h11-003
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein metabolism in human apolipoprotein B100transgenic/brown adipose tissue deficient mice: a model of obesity-induced hyperinsulinemia

Abstract: Obese and diabetic humans display decreased plasma high-density lipoprotein cholesterol (HDL-C) concentrations and an increased risk for coronary heart disease. However, investigation on HDL metabolism in obesity with a particular emphasis on hepatic ATP-binding cassette transporter A1 (ABCA1), the primary factor for HDL formation, has not been well studied. Human apolipoprotein B100 transgenic (hApoB tg ) and brown adipose tissue deficient (BATless) mice were crossed to generate hApoB tg /BATless mice. Male a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Indirect sandwich ELISAs were performed for apoA‐I (Fine Biological Technology; Whuan, China), SAA (R&D Systems; Minneapolis, MN), monocyte chemoattractant protein‐1 (MCP‐1) (R&D Systems; Minneapolis, MN), PON1 (Bosterbio; Pleasanton, CA), and tumor necrosis factor alpha (TNF‐α) (eBioscience; Vienna, Austria). Pooled serum samples were fractionated by fast protein liquid chromatography (FPLC) to evaluate lipoprotein cholesterol distribution using methods previously reported …”
Section: Methodsmentioning
confidence: 99%
“…Indirect sandwich ELISAs were performed for apoA‐I (Fine Biological Technology; Whuan, China), SAA (R&D Systems; Minneapolis, MN), monocyte chemoattractant protein‐1 (MCP‐1) (R&D Systems; Minneapolis, MN), PON1 (Bosterbio; Pleasanton, CA), and tumor necrosis factor alpha (TNF‐α) (eBioscience; Vienna, Austria). Pooled serum samples were fractionated by fast protein liquid chromatography (FPLC) to evaluate lipoprotein cholesterol distribution using methods previously reported …”
Section: Methodsmentioning
confidence: 99%
“…Overproduction of large VLDL 1 is driven by increased flux of nonesterified fatty acids from adipose tissue, upregulation of sterol regulatory element binding protein-1c (SREBP-1c), chronic stimulation of de novo lipogenesis, and reduced fatty acid oxidation in the liver [1][2][3][4]. Circulating HDL levels are maintained by hepatic ABCA1 [5], insulin resistance causes loss of hepatic ABCA1 protein expression [5][6][7][8][9] and a strong reciprocal relationship exists between ABCA1 expression and hepatic VLDL output [10][11][12][13], integrating triglyceride and cholesterol lipoprotein metabolism. Dysregulated hepatic lipid metabolism also contributes to non-alcoholic fatty liver disease (NAFLD), present in 70-80% of diabetic and obese patients [14], and a condition which ranges from simple steatosis (SS) to steatosis combined with necrosis and inflammation (non-alcoholic steatohepatitis; NASH) which can progress to hepatic fibrosis and cirrhosis [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Some research reported that dietary supplement of Curcumin with moderated intake of alcohol increased cholesterol efflux mediated by ABCA1 [20,21]. However, according to a recent study, hepatic ABCA1 may not be the main contributing factor of HDL metabolism in a model of obesity-induced hyperinsulinemia using human apolipopretein B100 transgenic/brown adipose tissue deficient mice [22]. Thus, there is still controversy about the role of ABCA1 in regulating the HDL-cholesterol level.…”
Section: Introductionmentioning
confidence: 99%